2000
DOI: 10.1002/1097-4644(20001215)79:4<672::aid-jcb150>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human endothelial cells on Human Bone Marrow Stromal Cell phenotype: Role of VEGF?

Abstract: Angiogenesis is a tightly regulated process involved in growth, repair, and bone remodeling. Several studies have shown that there is a reciprocal regulation and functional relationship between endothelial cells and osteoblast-like cells during osteogenesis, where systemic hormones and paracrine growth factors play an active role. Angiogenesis is induced by a variety of growth factors; among them vascular endothelial growth factor (VEGF) may be an important mediator for the angiogenic process involved in bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
187
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 56 publications
17
187
3
1
Order By: Relevance
“…VEGF-A expression in maturation stages of osteochondral cells was significantly increased 28 days after ESW treatment. These findings support previous studies that VEGF is responsible for hypertrophied cartilage neovascularization [4,38]. In our study, intensive TGF-P1 and VEGF-A expression in defect tissue suggests that their production is directly or indirectly promoted by physical stimulation provided by ESW treatment, and that TGF-P1 and VEGF are actively involved in recruitment and differentiation of mesenchymal stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…VEGF-A expression in maturation stages of osteochondral cells was significantly increased 28 days after ESW treatment. These findings support previous studies that VEGF is responsible for hypertrophied cartilage neovascularization [4,38]. In our study, intensive TGF-P1 and VEGF-A expression in defect tissue suggests that their production is directly or indirectly promoted by physical stimulation provided by ESW treatment, and that TGF-P1 and VEGF are actively involved in recruitment and differentiation of mesenchymal stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…Cell therapy induces neurorestorative changes in the brain reflective of several mechanisms of action; however, the ability of MSCs to localize to a region of brain injury and increase local concentrations of growth factors such as BDNF and VEGF may be paramount (Villars et al, 2000. Various cell concentrations and routes of administration have been applied to demonstrate the therapeutic efficacy of MSC treatment of neural injury .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have shown the capacity to differentiate into neurons and astrocytes and have the ability to preferentially migrate to damaged cortex (Kopen et al, 1999). Of particular significance is the ability of MSCs to secrete or stimulate secretion of growth factors which create a local environment conducive for neuroregeneration (Villars et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both are known to drive an increased expression of this marker in early time points. [30][31][32][33][34][35] Double stranded DNA (dsDNA) quantification showed that the stem cell spheroids produced in different coculture procedures presented approximately three times more dsDNA than the control conditions (cultured as monocultures in either α-MEM or M199) ( Figure 1c). Similar results were previously reported for other indirect coculture methods, where stem cell proliferation was increased via coculture with osteoblast cells [30,31] and HUVEC cells.…”
Section: Resultsmentioning
confidence: 99%